Persepsi Pegawai Terhadap Kehadiran Calo Layanan Administrasi Pada Dinas Kependudukan Dan Catatan Sipil Kabupaten Bima - M.Ulfatul Akbar Jafar; M. Taufik Rachman; Dedy Iswanto (UNIVERSITAS MUHAMMADIYAH MATARAM, 2020)
Public interest in the community is the main target in public service providers. Officials of the Office of Population and Civil Registry as a bureaucrat at the regional level are required to be able to handle the constraints faced in the government's promoted development efforts. Officials of the Office of Population and Civil Registration must be able to carry out its first function is to provide services to the community well, deft, effective and efficient. Another problem that often arises is the discipline of employees in providing services this proved many employees who come not on time, start the service not on time, rest not in time, and employees also home before the time to go home. This also greatly affects the service because if the shortage of employees then the counter service that will be opened also a little, so that the impact of many people who are not served. The purpose of this research are; 1) To know Employee Perception Against Attendance of Administration Service Bureau at Department of Population and Civil Regent of Bima Regency; 2) To know the Factors that may affect the Presence of Calo Administration Services At the Department of Population and Civil Registration Bima District.This research uses qualitative approach method with technique of determination of informant use Purposive sampling, meaning intentionally intake technique. Methods of data collection ie observation, interview (Interview) and documentation. Data type is qualitative data and sourced from secondary and primary data with data analysis technique Data Reduction, Data Presentation (Data Display), and Conclusion drawing / verification.The result of research shows that: The distance of the Office of Population and Civil Registry of Bima Regency is far and there is no public transportation passing through it. So that has a private vehicle that many do service in the Department of Population and Civil Registry Bima District, for people living in remote areas usually take care of services, especially the service of birth certificate by handing someone close to his relationship with bureaucracy or brokers even if they have to pay more. The presence of brokers is difficult to separate from public services. But now their existence began to decrease, because the government increasingly simplify the process of document management and licensing.)